2018
DOI: 10.14814/phy2.13674
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 polyunsaturated fatty acid supplementation reduces blood pressure but not renal vasoconstrictor response to orthostatic stress in healthy older adults

Abstract: Older adults exhibit augmented renal vasoconstriction during orthostatic stress compared to young adults. Consumption of omega‐3 polyunsaturated fatty acids, such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) found in fish oil (FO), modulates autonomic nerve activity. However, the effect of omega‐3 polyunsaturated fatty acid consumption on the renal vasoconstrictor response to orthostatic stress in young and older adults is unknown. Therefore, 10 young (25 ± 1 years; mean ± SEM) and 10 older (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
(108 reference statements)
0
3
0
Order By: Relevance
“…Interest in how dietary ω3 PUFAs influence several physiological (eg, ageing) or pathological (eg, cardiovascular disease) conditions has grown considerably over the past decade. Numerous clinical studies have focused mainly on the anti-inflammatory properties of ω3 PUFAs as well as on their neuroprotective and regenerative effects 71–74. In particular, one review analysed human brain MRI studies and experimental studies and confirmed that ω3 PUFAs can protect the brain during ageing by preventing peroxidation, inflammation and excitotoxicity; modulating neurotransmission; and increasing neurogenesis, thereby improving the brain’s ‘coping’ mechanisms during ageing 75…”
Section: Discussionmentioning
confidence: 99%
“…Interest in how dietary ω3 PUFAs influence several physiological (eg, ageing) or pathological (eg, cardiovascular disease) conditions has grown considerably over the past decade. Numerous clinical studies have focused mainly on the anti-inflammatory properties of ω3 PUFAs as well as on their neuroprotective and regenerative effects 71–74. In particular, one review analysed human brain MRI studies and experimental studies and confirmed that ω3 PUFAs can protect the brain during ageing by preventing peroxidation, inflammation and excitotoxicity; modulating neurotransmission; and increasing neurogenesis, thereby improving the brain’s ‘coping’ mechanisms during ageing 75…”
Section: Discussionmentioning
confidence: 99%
“…ELOVL7 participates in elongating fatty acids [ 35 ], which have been implicated in blood pressure control. A recent trial showed that long-chain Omega-3 polyunsaturated fatty acid supplementation reduced blood pressure fall after undergoing graded lower-body negative pressure [ 36 ]. Omega-3 fatty acid supplementation did not change muscle sympathetic nerve activity at rest but augmented sympathetic outflow in response to physiological stressors such as the ischemic handgrip or cold pressor test [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that one mechanism involved could be the modulation of proinflammatory IL-6, whose levels were higher in the eSS-and the AA-treated rats, but not in the EPA-treated and the Wi rats, following HNaD feeding. It has been shown that ω-3 fatty acids such as EPA, have beneficial impacts on multiple risk factors linked to T2-DM including blood pressure, as they benefit the heart and blood vessel functions, as well as the blood lipids due to their antithrombotic, anti-inflammatory and anti-oxidative actions (41). In particular, the anti-inflammatory effects of EPA are mediated through the reduction of arachidonic acid (AA)-derived inflammatory mediators, the activation of the nuclear receptor peroxisome proliferator-activated receptor γ (PPARγ), the G-proteincoupled receptor (GPR) 120 as an agonist (42), and stimulation of the AMPK/SIRT pathway (43).…”
Section: Discussionmentioning
confidence: 99%